Core Correctional Practices in Community Supervision: An Evaluation of a Policy Mandate to Increase Probation Officer Use of Skills - Viglione, Jill (International journal of offender therapy and comparative criminology, 2021)
Community supervision officer training programs aim to translate core correctional practices into routine practice. These training programs emphasize skill-building designed to shift supervision strategies from law enforcement/compliance-oriented to a focus on promoting and supporting behavior change. Despite evidence of their effectiveness, research finds trained officers use newly learned skills infrequently. The current study examined the impact of a policy, implemented post-training, designed to encourage trained officers to use skills emphasized by the Staff Training Aimed at Reducing Rearrest (STARR) training program more frequently. The current study examined the effectiveness of this policy on the frequency and type of skills used by officers in their interactions with individuals on their caseload. Analyses suggested the policy mandate was effective in increasing skill use, however officers still used trained skills in less than half of their interactions. Implications and considerations for increasing the use of skills are discussed.